(untitled) (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: This research aimed to evaluate in vitro ruminal fermentation, methane (CH4 ) emissions, and the relationship between the nutritional content and CH4 emissions of tropical feedstuffs to formulate low CH4 -emitting feeds for ruminants. Materials and Methods: Eighteen feedstuffs, including roughages (3 crop residues, 2 silages, 3 common grasses, and 4 leguminous fodder) and 6 concentrates, were evaluated using the Hohenheim Gas Test. Approximately 200 mg of feed were incubated with a rumen fluid-buffer solution for 72 h to test gas production (GP) and 120 mg for 24 h to determine the CH4 concentration in the gas. Digestibility of organic matter (dOM) and metabolizable energy (ME) were calculated using GP data. Results: Leguminous fodder contained the highest crude protein (CP) concentration (166–314 gm/kg dry matter (DM)), followed by common grasses (52–147 gm/kg DM) and silages (94–106 gm/kg DM), but the lowest concentration of detergent fiber fractions. Crushed wheat and maize had higher dOM and ME (87.8% and 90.9%, and 14.4 MJ/kg DM and 13.8 MJ/kg DM, respectively), and their CH4 concentration (% of GP) and CH4 emissions(L CH4 /kg dOM) followed a similar trend asthe other feedstuffs. The dOM and ME of German grass and Ipil-ipil were higher, whereas the CH4 concentration and CH4 emissions were lower compared to crop residues and other common grasses. The CH4 emissions originating from the feedstuffs were positively correlated with the concentration of neutral detergent fiber and GP and negatively correlated with CP. Conclusion: Our result provides an opportunity to select feed ingredients with higher digestibility and concurrently less CH4 emissions in formulating diets for ruminants when using commonly available feed resources in many tropical countries. This may enhance animal productive performances while reducing the impact of animal production on the environment. J. Adv. Vet. Anim. Res., 11(4): 924–935, December 2024 http://doi.org/10.5455/javar.2024.k842